2003
DOI: 10.1053/jhep.2003.50307
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Pparα–Dependent Hepatic Lipid Turnover in Dietary Steatohepatitis in Mice

Abstract: We have proposed that steatohepatitis results from reactive oxygen species (ROS) acting on accumulated fatty acids to form proinflammatory lipoperoxides. Cytochrome P450 4a (Cyp4a) and Cyp2e1 are potential hepatic sources of ROS. We tested the hypothesis that increasing Cyp4a through activation of peroxisome proliferator-activated receptor ␣ (PPAR␣) should aggravate steatohepatitis produced by feeding a methionine and choline deficient (MCD) diet. Conversely, we assessed dietary steatohepatitis in PPAR␣ ؊/؊ mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
351
3
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(392 citation statements)
references
References 48 publications
33
351
3
5
Order By: Relevance
“…In the CCl 4 therapeutic model, the rank order of antifibrotic efficacy was IVA337 ≥ fenofibrate > rosiglitazone > GW501516, with PPARγ and PPARδ agonists having a partial effect on fibrosis. Our results are consistent with published studies on the effect of selective PPAR agonists on liver fibrosis 14, 21, 39. However, results with GW501516 in our study and in the literature differ from those obtained with KD3010, another PPARδ agonist that was shown to be very active on liver fibrosis induced by CCl 4 or bile duct ligation 39.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the CCl 4 therapeutic model, the rank order of antifibrotic efficacy was IVA337 ≥ fenofibrate > rosiglitazone > GW501516, with PPARγ and PPARδ agonists having a partial effect on fibrosis. Our results are consistent with published studies on the effect of selective PPAR agonists on liver fibrosis 14, 21, 39. However, results with GW501516 in our study and in the literature differ from those obtained with KD3010, another PPARδ agonist that was shown to be very active on liver fibrosis induced by CCl 4 or bile duct ligation 39.…”
Section: Discussionsupporting
confidence: 90%
“…PPARα‐ as well as PPARγ‐deficient mice are more sensitive to the development of steatohepatitis under an MCD than wild‐type mice 21, 22. Using selective PPAR agonists, it was reported that Wy‐14,643 (a PPARα agonist), GW501516 (a PPARδ agonist), and PPARγ activation by pioglitazone prevent and/or reverse MCD‐induced steatohepatitis 21, 22, 23, 24, 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARα is a ligand-activated transcription factor involved in fatty acid metabolism [47]. Earlier evidence indicated that PPARα −/− mice had severe hepatic steatosis [48]. In particular, several genes upregulated by PTE, such as Lpin-1, Pctp, and Abcg5, were direct target genes of PPARα [49].…”
Section: Discussionmentioning
confidence: 99%
“…14 The fact that CYP2E1-null mice also developed liver injury was attributed to compensatory mechanisms, including the induction of CYP4A isozymes. 27,28 However, the role of CYP4A10 and CYP4A14 in the generation of LPO products and ROS has been controversially discussed 29 ; Bradford et al 14 did not find increased oxidative DNA damage in CYP2E1-null mice despite elevated CYP4A enzyme levels.…”
Section: Discussionmentioning
confidence: 99%